819. 1) 3(x - 2) 3) 5(y + 3) = 10;
5) -4(x - 2) = -6;
2) 6(z - 1) = 18;
4) 3(2x - 7) = 9;
6) 3(x - 5) = x + 3.​

YeezyM YeezyM    3   14.01.2021 10:49    2

Ответы
киска555555544 киска555555544  13.02.2021 10:50

3) у=-1

5) х= 3,5

2)z=4

4) x=5

6)x=9

Пошаговое объяснение:

3)5у+15=10

5у=-5

у=-1

5)-4(х-2)=-6

- 4х+8=-6

- 4х=-14

х= 3,5

2)6(z-1)=18

6z-6=18

6z=24

z=4

4)3(2x-7)=9

6x-21=9

6x=30

x=5

6)3(x-5)= x+3

3x-15=x+3

3x-x=3+15

2x=18

x=9

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика